2011
DOI: 10.1089/jpm.2010.0302
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Pain in Nonresponsive Hospice Patients: Development and Preliminary Testing of the Multidimensional Objective Pain Assessment Tool (MOPAT)

Abstract: The MOPAT has preliminary evidence of reliability, validity, and clinical utility. Full-scale psychometric testing in hospice and acute care hospital patients is currently underway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…The potential translational utility of this approach is also demonstrated by the recent BOLD imaging study showing analogous activation of the NAc in rats in response to pain onset and offset as described in humans [11]. Additionally, it is noted that there are circumstances in humans where determining whether pain is present is difficult, including schizophrenia, Alzheimer’s, mental retardation, elderly or young children including neonatal patients [4; 35; 42; 63; 67]. In these individuals, ongoing pain might be unmasked with imaging the activation of this circuit with a transient pain relieving intervention allowing for appropriate decisions in medical management of the patient.…”
Section: Discussionmentioning
confidence: 98%
“…The potential translational utility of this approach is also demonstrated by the recent BOLD imaging study showing analogous activation of the NAc in rats in response to pain onset and offset as described in humans [11]. Additionally, it is noted that there are circumstances in humans where determining whether pain is present is difficult, including schizophrenia, Alzheimer’s, mental retardation, elderly or young children including neonatal patients [4; 35; 42; 63; 67]. In these individuals, ongoing pain might be unmasked with imaging the activation of this circuit with a transient pain relieving intervention allowing for appropriate decisions in medical management of the patient.…”
Section: Discussionmentioning
confidence: 98%
“…The MOPAT was modified to serve as a measure of two dimensions of pain (Behavioral and Physiologic) that could be used in non-communicative individuals across palliative care settings. In the original formulation, the developers included a third dimension, Sensory, focusing on the temporal pattern of pain 56 . The Behavioral Dimension is comprised of four behaviors scored on a scale of 0 (no behavior displayed) to 3 (most severe behavior): 1) Restlessness , 2) Tense muscles , 3) Frowning/grimacing , and 4) Patient Sounds , which are summed for a Behavioral Dimension score ranging from 0-12.…”
Section: Review Of Selected Pain Assessment Toolsmentioning
confidence: 99%
“…The Sensory Dimension is designed to assess pattern of pain by using Behavioral and Physiologic ratings over time, in conjunction with knowledge of pain etiology, to choose among three groups of adjectives adapted from the McGill Pain Questionnaire Long Form (brief/momentary/transient; rhythmic/periodic/intermittent; continuous/steady/constant). Several small-scale developmental studies that were conducted in inpatient hospice settings demonstrated initial evidence of reliability, validity, and clinical utility of the Behavioral and Physiologic dimensions, but little use of the Sensory dimension 56 . These results led to full-scale psychometric evaluation of a revised MOPAT consisting of Behavioral and Physiologic dimensions in both the acute care hospital and inpatient hospice settings.…”
Section: Review Of Selected Pain Assessment Toolsmentioning
confidence: 99%
“…The behavioral responses to pain can be misinterpreted by others, especially health providers (Wilkie, Berry et al, 2010). Well-known examples of pain-related behaviors include behaviors to control the pain such as preventing it, reducing it through positions, reporting it, and taking analgesics (Wilkie, Keefe, Dodd, & Copp, 1992), some of which have informed behavioral assessment tools for persons not able to communicate their pain (McGuire, Reifsnyder, Soeken, Kaiser, & Yeager, 2011). Other behavioral responses include interference with activities of daily living (Goebel et al, 2009; Vallerand et al, 2007), can be complex, and involve caregivers.…”
Section: Critical Evidence and Issuesmentioning
confidence: 99%